16.7 W 885 nm diode-side-pumped actively Q-switched Nd:YAG/YVO4 intracavity Raman laser at 1176 nm. (26th October 2017) - Jiang, Pengbo; Zhang, Guizhong; Liu, Jian; Ding, Xin; Sheng, Quan; Yu, Xuanyi; Sun, Bing; Shi, Rui; Wu, Liang; Wang, Rui; Yao, Jianquan
Abstract: We proposed and experimentally demonstrated the generation of high-power 1176 nm Stokes wave by frequency shifting of a 885 nm diode-side-pumped Nd:YAG laser using a YVO4 crystal in a Z -shaped cavity configuration. Employing the 885 nm diode-side-pumped scheme and the Z -shaped cavity, for the first time to our knowledge, we realized the thermal management effectively, achieving excellent 1176 nm Stokes wave consequently. With an incident pump power of 190.0 W, a maximum average output power of 16.7 W was obtained at the pulse repetition frequency of 10 kHz. The pulse duration and spectrum linewidth of the Stokes wave at the maximum output power were 20.3 ns and 0.08 nm, respectively.